PELAKSANAAN PROMOSI TIKET PESAWAT DI PT RIAU KARSA PELITA PEKANBARU - Dwika Rahmadina Putri; Mariaty Ibrahim; Andi M Rifiyan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
The purpose of this research is to know how the implementation of airlines tickets promotion in PT Riau Karsa Pelita Pekanbaru and respondents reaction about the implementation of airlines tickets promotion.This research is using descriptive quantitative methods. There are 100 sample of people is taken for accidental sampling. The data collection techniques in this research is using observation, interview, and quesionnaires. The likert scale uses to know how long or short intervals to generate quantitative data.The result of the research shows that PT Riau Karsa Pelita Pekanbaru has implemented airlines tickets promotion by using the promotion mix: Advertising, Sales Promotion, and Personal Selling. According to respondents, the implementation of airlines tickets promotion in PT Riau Karsa Pelita Pekanbaru is still needed to be improved.Keywords: promotion, airlines tickets, promotion mix